SISTEM INFORMASI KEUANGAN SEKOLAH BERBASIS WEBSITE MENGGUNAKAN METODE PROTOTYPE PADA SMAN 2 CIKARANG PUSAT - Dodi Hendarman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
With the development of internet technology, it makes it easier for humans to do work. Many ways or systems from a job that is still done manually (conventionally) are changed to computerized so that it is more effective and efficient. One of them is in the financial management system at SMAN 2 Cikarang Pusat which can be done using a computerized system. The method used is the prototype method, which is a software development method, which is a physical model of the system's work and serves as an initial version of the system. With this prototyping method, a prototype system will be produced as an intermediary for developers and users so that they can interact in the process of information system development activities. The purpose of this study is to build a financial management system for SMAN 2 Cikarang Pusat, which is expected to assist officers in managing school finances more regularly, effectively and efficiently. The results achieved from the design and manufacture of this financial management system are assisting financial officers in the process of data collection, reporting, and filing of finances as well as introducing developed information technology.